Molecular mechanism underlying Oleum Cinnamomi-induced ferroptosis in MRSE via covalent modification of AhpC - Wang, Jianchao; Wu, Ziqi; Chen, Qianying; Yan, Danna; Ling, Yuanqiang; He, Yuan; Jin, Lu; Zhao, Guomin; Peng, Huayong; Yang, Depo (Frontiers in Pharmacology, 2025)
IntroductionOleum Cinnamomi (OC) is a volatile oil extracted by steam distillation from the dried branches and leaves of Cinnamomum cassia Presl, a plant belonging to the Lauraceae family. For centuries, OC has been utilized as a food preservative and flavoring agent, demonstrating potent inhibitory effects against bacteria and fungi. It is particularly effective in controlling infections caused by Methicillin-Resistant Staphylococcus epidermidis (MRSE), which often parasitizes the skin surface. To uncover the target and molecular mechanism by which OC eradicates MRSE, this study initially assessed the impact of OC and its primary constituents on oxidative stress in MRSE cells.MethodsMass spectrometry was employed to identify the target and covalent binding sites of OC, while a kit was used to monitor changes in key biomolecules of MRSE cells exposed to OC. Additionally, the efficacy of OC in inhibiting MRSE adhesion and infection of RAW 264.7 mouse macrophages was evaluated.ResultsThe findings revealed that OC’s main components, cinnamaldehyde and 2-methoxycinnamaldehyde, covalently modify MRSE and AhpC. This modification disrupts the AhpC-AhpE regeneration cycle, thereby disturbing both enzymatic and non-enzymatic redox homeostasis. It leads to intracellular ROS accumulation and effectively prevents MRSE from adhering to RAW 264.7 mouse macrophages. In response to ROS detoxification, MRSE attempts to upregulate the expression of TCA cycle-related proteins. However, the continuous accumulation of ROS inactivates the [Fe-S] protein of Aconase (ACO), hindering ACO’s catalytic conversion of citric acid to isocitrate. This results in sustained intracellular accumulation of citric acid, limiting the TCA cycle and ATP generation. Simultaneously, enzymes involved in reduction catalysis, such as superoxide dismutase (SOD), peroxidase reductase (Prx), and glutathione synthase (GCL), are collectively inactivated. OC induces oxidative stress in MRSE, depleting GSH and triggering lipid peroxidation, which in turn induces MRSE to undergo ferroptosis.DiscussionThis covalent inhibition strategy targeting AhpC to induce ferroptosis offers a promising approach for effectively treating and preventing MRSE infections, thereby opening new avenues for combating drug-resistant pathogen infections.